Field notes, Winter 1977-1978 - Black, Gladyset al (1977)
Compilation of bird sightings throughout Iowa for the Winter of 1977-1978 submitted by Gladys Black. The bird species listed are the White-winged Crossbill, the Red Crossbill, the Pine Grosbeak, and the Snowy Owl. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed